EFEITO DO MANEJO ARTIFICIAL DA DESRAMA NO DESEMPENHO SILVICULTURAL DE EUCALIPTO EM SISTEMA SILVIPASTORIL - VILELA, Luiz Renato Santos; ANGELES, Rafael Ruffato de; FREITAS, Gabriela da Silva; RODRIGUES, Carolina Garcia; LIMA, Isabela Machado de Oliveira; MARQUES FILHO, Wolff Camargo; BARBOSA, Giselle Feliciani (ANAIS DO ENIC, 2020)
-